The Dilemma in COVID-19 Pandemic: The Protection of Intellectual Property Rights or A Life? - Kristin, Debby; Dewi, Chloryne Trie Isyana (Media Iuris, 2022)
AbstractAccess to medicines and health facilities is a form of fulfillment of the right to health which, if not fulfilled, will result in the loss of the right to life. During the time of COVID-19 that hit the whole world, data released by WHO stated that 4,592,934 people had died from COVID-19, and the number was growing globally every day. However, only 5,352,927,296 doses of vaccines have been administered worldwide, with most going to developed countries. Experts predict the global population will be fully vaccinated by at least September 2023. WHO research shows that through vaccination, the rate of transmission of the disease can be reduced, and even if the subject is infected, vaccination can still reduce mortality and severity. However, its manufacture and distribution are protected by several intellectual property rights (IPR) legal instruments, which have resulted in several Global South countries, especially Indonesia being late in the vaccination process. This article aims to criticize how vaccine distribution is hampered due to regulations related to IPR, namely patents and trade secret. The author uses normative juridical research methods to answer the problems in this study by focusing on literature research and secondary data related to vaccination and the right to health which have implications for the right to human life. Comparison with other countries, especially South Africa fighting HIV/AIDS for years using the flexibilities of TRIPs, is also the subject of this research. This research describes how the Global North countries have a significant role in distributing the COVID-19 vaccine to the Global South. The delay in allotment due to regulations related to Intellectual Property Rights causes violations of several fundamental rights.Keywords: Bankruptcy; Insolvency Test; Principle of Balance.